Characterization of forsterite bioceramics - Sara Lee, K.Y; Christopher Chin, K.M.,; Ramesh, Singh; Tan, Chou Yong; Teng, Wan Dung; Sopyan, Iis (2012)
The present work is on the synthesis of forsterite (Mg2SiO4) powder using talc and magnesium oxide powders as the starting materials followed by a heat treatment process. Sintering behavior and mechanical properties of the forsterite bodies were evaluated from 1200ºC to 1500°C. Forsterite phase were detected in samples without any secondary phases at all sintering temperatures. A very high fracture toughness of 4.9MPa.m1/2 and Vickers hardness of 7.1GPa were measured for samples sintered at 1400°C, thus indicating the viability of this ceramic for biomedical application.